Enhancement of Ministry of International Trade and Industry (MITI) groom big program (SME, Biscuits Industry:Johor) / Noraida Md Salleh, Nuryakizah Yahaya dan Umi Melati Ab Malik - Md Salleh, Noraida; Yahaya, Nuryakizah; Malik, Umi Melati (2010)
Small to Medium-sized Manufacturing Enterprise (SME) has consistently demonstrated innovate and bring to the market new technologies and advancement in manufacturing. Industrialized nations function as the supplier base for domestic manufacturing. However, as SMEs are going global, SMEs face a new challenge in competing in the competitive global this research, we aim to answer the following question: by taking advantage of the new opportunities, how SMEs can reposition themselves to be more competitive in the market. We analyze the data collected from over 7 SMEs biscuits industry and consumers. The information about SMEs' importance and practice of Halal, HACCP and GMP. We are able to compare between SMEs importance and practices with consumers Halal and GMP elements. This information can be used to help SMEs better understand and opportunities confronting their operations. So their business transformations can be conducted for more competitive edges. The food content, it is more meaningful if the quality standard assures that food is suitable for processed in a hygiene manner, is nutritious and safe. This paper will focus on the CCP and Halal in terms of quality standards that are necessary to be given consideration in information of food. This paper focused on 7 SMEs who had joined the Groom Big Program 2010. In the survey, we suggested the enhancement model Groom Big model to be implemented by MITI in order to equip SMEs to be more competitive and successful in future. Total Quality Management Process, Small to Medium-sized Manufacturing, Good Ordering Practice, Hazard Analysis and Critical Control Point, Halal, SIRIM, Malaysian Approach, Quality Assurance, Groom Big and The Malaysian Administrative Moderation Planning Unit (MAMPU).